2004
DOI: 10.1097/01.ju.0000144640.26182.41
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal or Extraperitoneal Laparoscopic Radical Prostatectomy: Does the Approach Matter?

Abstract: : ELRP is superior to TLRP with respect to operative time, hospitalization and early continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 16 publications
1
55
0
1
Order By: Relevance
“…However, Eden et al reported that urinary continence happened earlier with the extraperitoneal approach due to larger dissection and consequent bladder denervation that occurs in the transperitoneal approach (23). In relation to sexual potency, results were quite satisfactory, which can be explained by the clear identification of the pedicle and the use of clip in the prostate pedicles, thus preventing the heat to be transmitted to the neurovascular bundle.…”
Section: Commentsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, Eden et al reported that urinary continence happened earlier with the extraperitoneal approach due to larger dissection and consequent bladder denervation that occurs in the transperitoneal approach (23). In relation to sexual potency, results were quite satisfactory, which can be explained by the clear identification of the pedicle and the use of clip in the prostate pedicles, thus preventing the heat to be transmitted to the neurovascular bundle.…”
Section: Commentsmentioning
confidence: 86%
“…Mean age was 66 years (55-73), with mean body mass index of 24 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Twenty-five (89.3%) had ASA surgical risk II and 3 patients were ASA I (10.7%).…”
Section: Between February 2001 and February 2004mentioning
confidence: 99%
“…Some authors prefer the transperitoneal approach based on the larger working space and better luminosity and others prefer the extraperitoneal counterpart, based on the lack of contact with the intraperitoneal organs (3)(4)(5)(6).…”
Section: Clinical Urology Doi: 101590/s1677-55382010000400008mentioning
confidence: 99%
“…8,[55][56][57][58][59][60][76][77][78][79][80] Table 1 shows urinary continence rates for RRP and LRP, defined as no need for any pads or "protection." Table 2 shows the sexual potency rates.…”
Section: Urinary and Sexual Functionmentioning
confidence: 99%